Exploring genetic diversity and variation of Ovar-DRB1 gene in Sudan Desert Sheep using targeted next-generation sequencing - Salim, B.; Nakao, R.; Chatanga, E.; Marcuzzi, O.; Eissawi, M.A.; Almathen, A.; Hanotte, Olivier H.; Giovambattista, G. (Springer, 2024)
Introduction The Ovar-DRB1 gene, a crucial element of the Major Histocompatibility Complex (MHC) Class II region, initiates adaptive immunity by presenting antigens to T-cells. Genetic diversity in sheep, particularly in MHC Class II genes like Ovar-DRB1, directly influences the specturm of presented antigens impacting immune responses and disease susceptibility. Understanding the allelic diversity of Ovar-DRB1 gene in Sudan Desert Sheep (SDS) is essential for uncovering the genetic basis of immune responses and disease resistance, given the breeds significance in Sudan's unique environment. Methods Utilizing Targeted Next-Generation Sequencing (NGS) we explore allelic diversity in Ovar-DRB1 gene within SDS. Successfully ampliying and sequencing the second exon of this gene in 288 SDS samples representing six breeds provided a comprehensive allelic profile, enabling a detalied examination of the gene's genetic makeup. Results We identifed forty-six alleles, including four previously unreported, enrichness the genetic diversity of SDS breeds. These alleles exhibiting non-uniform distribution, varying frequencies across breeds, indicating a breed-specific genetic landscape. Certain alleles, known and novel, show higher frequencies in specific populations, suggesting potential associations with adaptive immune responses. Identifying these alleles sets the stage for investigating their functional roles and implications for disease resistance. Genetic differentiation among SDS breeds, as indicated by FST values and clustering analyses, highlights a unique genetic makeup shaped by geographic and historical factors. These differentiation patterns among SDS breeds have broader implications for breed conservation and targeted breeding to enhance disease resistance in specific populations. Conclusion This study unveils Ovar-DRB1 gene allelic diversity in SDS breeds through targeted NGS and genetic analyses, revealing new alleles that underscore the breeds’ unique genetic profile. Insights into the genetic factors governing immune responses and disease resistance emerge, promising for optimization of breeding strategies for enhanced livestock health in Sudan’s unique environment.